2022
DOI: 10.1123/ijsnem.2021-0335
|View full text |Cite
|
Sign up to set email alerts
|

“Food First but Not Always Food Only”: Recommendations for Using Dietary Supplements in Sport

Abstract: The term “food first” has been widely accepted as the preferred strategy within sport nutrition, although there is no agreed definition of this and often limited consideration of the implications. We propose that food first should mean “where practically possible, nutrient provision should come from whole foods and drinks rather than from isolated food components or dietary supplements.” There are many reasons to commend a food first strategy, including the risk of supplement contamination resulting in anti-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 117 publications
(155 reference statements)
1
46
0
1
Order By: Relevance
“…To achieve the recommended amounts of nutrients in the diet of an athlete, and due to the difficulty in consuming large meals immediately after exercise, periodic supplementation with supplements, especially from group A according to the Australian Institute of Sport (AIS), may be considered. According to recent reports, food-first but not always food-only [ 58 ] football players in special cases should develop a personalized nutrition and supplementation plan via collaboration with their dietitian to optimize their performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve the recommended amounts of nutrients in the diet of an athlete, and due to the difficulty in consuming large meals immediately after exercise, periodic supplementation with supplements, especially from group A according to the Australian Institute of Sport (AIS), may be considered. According to recent reports, food-first but not always food-only [ 58 ] football players in special cases should develop a personalized nutrition and supplementation plan via collaboration with their dietitian to optimize their performance.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes with low 25-(OH)D levels (<30 ng/mL or <75 nmol/L) have also been shown to be at a higher risk of injury, including musculoskeletal injuries [ 64 ]. Close et al [ 58 ] proposed recommendations for using dietary supplements in sport food-first but not always food-only. Authors have suggested several reasons why a food-only approach may not always be optimal for athletes, one of which concerns vitamin D [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although micronutrient deficiencies are common in the community [5], athletes may have elevated risks due to increased nutrient turnover [3] and/or sub-optimal vitamin/mineral consumption [6]. Since micronutrients play central roles in numerous bodily functions, including energy production, gene transcription, bone health, immunity, and inflammatory responses [3,[7][8][9][10], deficiencies can…”
Section: Introductionmentioning
confidence: 99%